Multiple Biliary Papillomatosis. Issue 2 (1992) - Tireli, Mustafa; Uslu, Adam
Abstract : Diffuse biliary papillomatosis is a rare bile duct tumour. We report a case of multiple biliary papillomatosis treated surgically with a transhepatic stent. Diffuse biliary papillomatosis involving intra and extrahepatic bile ducts is extremely rare. It is regarded as having low grade malignant potential. In this report a case of diffuse biliary papillomatosis with obstructive jaundice is presented.